Cash-for-care use and union dissolution in Finland - Morosow Kathrin; Jalovaara Marika; Härkönen Juho (Stockholm University Demography Unit, 2025)
Prominent theories have long suggested that couples’ gendered division of labor decreases the risk of separation. Family policies such as the Finnish cash-for-care (CFC) benefit, which is paid if a young child does not attend public daycare, may encourage a gendered division of labor, at least temporarily. Using Finnish register data, this study examines the effect of receiving the CFC benefit on the short- and long-term risks of separation. Discrete-time event history analyses suggest a lower separation risk while the benefit is taken, but no effect in the long term. Fixed-effects models for non-repeated events indicate postponement of separation during benefit take-up, as well as selection into longer periods of CFC use for couples with higher latent propensity to separate. It is concluded that the CFC benefit use, signaling a gendered division of labor, predicts a lower separation risk during receipt of the benefit but not beyond that period.